Intelligent Traffic System for Ambulance Using Fuzzy Control System - Nur Iksan; Eva Faza Sabela; Subiyanto; Muhammad Harlanu (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Congestion is a seemingly endless problem as vehicle increase is not followed by road width increase. One of the serious problems caused by congestion is ambulance delays in taking patients to the hospital, potentially causing dead on arrival. Therefore, an automatic traffic control system is needed to minimize the dead on arrival rate by prioritizing emergency vehicles, preventing them from being stuck in the traffic light congestion, and helping them to transport the patients faster to receive medical care. The present study designs an intelligent traffic light control system for ambulances using Fuzzy Control System. This traffic light control system was designed for a four-legged intersection using RFID to detect the ambulance load and an infrared sensor to detect the road condition based on the number of vehicles at the intersection. Values from RFID and infrared sensor are used as Fuzzy control system input to obtain the priority value of each lane. The priority value is then transmitted to ESP 32 server to turn the light green on the lane to be passed by the ambulance. If there is one line that has a priority value of 11 and line three has a priority value of 85, then the system will turn green on lane three. So it can be said that overall system performance is 100% optimally successful. This study proves that the fuzzy control system is the right method for determining priorities when a collision occurs between emergency vehicles.